Thermal confort of the laboratory in the Cuiabá University - Novais, Jonathan Willian Zangeski; Joaquim, Thiago D'Orazio; Almeida, Felipe Miguel de; Zuffo, Monica Natany; Nogueira, Marta Cristina de Jesus Albuquerque; Leal, Lydiane Abdon; Rodrigues, Alessandra Bittencurt Crestani; Kunz, Fernanda de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Because of high average air temperature during the year in Cuiaba-MT, there is a need to investigate the thermal comfort of the buildings of this city,thenaimed to analyze the thermal comfort of the laboratory at the University of Cuiabá, using temperatures given by globe thermometers, dry bulb, wet bulb and infrared, in the dry season and the rainy season. Collected data average surface temperature of the inner and outer walls where the outside front facade on the north position suffers from greater solar incidence, with variations throughout the year. The facades in Cuiabá directed to Southwest heat stroke are higher mainly in the afternoon between September and October, and to decrease the direct sun receiving the facades is recommended to use wipers in strategic positions, among other suggestions EPS of use and afforestation. Given the results of experimental tests demonstrated is the need to use heat mitigation strategies inside environments, especially in Cuiabá.